Phytotoxic activity and chemical composition of aqueous volatile fractions from Eucalyptus species. - Jinbiao Zhang; Min An; Hanwen Wu; De Li Liu; Rex Stanton (PLoS ONE, 2014)
The essential oils from four Eucalyptus species (E. spathulata, E. salubris, E. brockwayii and E. dundasii) have been previously confirmed to have stronger inhibitory effects on germination and seedling growth of silverleaf nightshade (Solanum elaeagnifolium Cav.). The aqueous volatile fractions (AVFs) were the water soluble volatile fractions produced together with the essential oils (water insoluble fractions) during the steam distillation process. The aim of this study was to further assess the phytotoxicity of AVFs from the four Eucalyptus species and their chemical composition. The fresh leaves of the four Eucalyptus species were used for the extraction of AVFs. The AVFs were tested for their phytotoxic effects on the perennial weed, silverleaf nightshade under laboratory conditions. The chemical compositions of the AVFs were determined by gas chromatograph-mass spectrometry (GC-MS). Our results showed that the AVFs had strong inhibition on the germination and seedling growth of silverleaf nightshade. The inhibition index increased with the increasing concentrations of AVFs. The inhibitory effects of the AVFs varied between different Eucalyptus species. The AVF from E. salubris demonstrated the highest inhibitory activity on the weed tested, with complete inhibition on germination and seedling growth at a concentration of 75%. The GC-MS analysis revealed that 1,8-cineole, isopentyl isovalerate, isomenthol, pinocarvone, trans-pinocarveol, alpha-terpineol and globulol were the main compounds in the AVFs. These results indicated that all AVFs tested had differential inhibition on the germination and seedling growth of silverleaf nightshade, which could be due to the joint effects of compounds present in the AVFs as these compounds were present in different quantities and ratio between Eucalyptus species.